Rainfall Causes Flooding In South Konawe Regency, Southeast Sulawesi, Indonesia - Fitra Sawfla Insani; Siska Shafrianti Pratiwi Darman; Evi Fitriani (Journal of Health Science and Pharmacy, 2025)
Background: Rainfall or precipitation is a crucial climatic phenomenon that significantly influences environmental conditions and ecosystems, including the occurrence of natural disasters such as floods. In Indonesia, extreme rainfall is a major contributing factor to flooding, particularly in flood-prone areas such as floodplains and downstream river regions. However, flood risks are increasingly shifting to upstream areas due to changes in land use, notably the expansion of human settlements along riverbanks. Flood occurrences are determined by multiple factors, including topographical slope, soil type, and the condition of water drainage systems. Objective: This study aims to determine the extent of rainfall that contributes to flood events in South Konawe Regency. Method: The research employs a descriptive analytical method to illustrate environmental health conditions by examining the relationship between atmospheric dynamics and rainfall patterns in South Konawe. The study involves an in-depth evaluation of flood events using both primary and secondary descriptive data. Data collection techniques include surveys and literature reviews. Results: According to the data, there were 194 rainy days recorded in 2018, with a total annual rainfall of 3.179.7 mm. The highest monthly rainfall was observed in June (644.6 mm), followed by May and December. Conclusion: Effective infrastructure management and the maintenance of drainage systems are essential for reducing flood risks in South Konawe Regency. Understanding the interplay between rainfall intensity, frequency, seasonal variations, and local geographical and infrastructural conditions is critical for planning flood prevention and mitigation strategies that safeguard both the population and the environment. Keywords: Rainfall, Flood, South Konawe Regency, Indonesia